The Domestic Veil: The Net Curtain in the Uncanny Home. (2nd July 2020) - Quarini, Carol
Abstract: In this practice-based research the net curtain embodies Freud's uncanny as the point of slippage between the homely and the unhomely. In this liminal role the net curtain is used to reconsider women's equivocal experience of home as sanctuary and prison, based on tropes from Victorian gothic novels, but with contemporary parallels. Considered as a domestic veil the net curtain is a metonym for the trapped heroine in those nineteenth-century, gothic novels that critique the notion of separate spheres and the conflation of women with their homes and domesticity. This study builds on research into the uncanny, the gothic and the domestic and the discourse of Mary Douglas and Julia Kristeva on the instability of margins, to reveal the dysfunction that results from breaching domestic boundaries. The net curtain gradually reveals the secrets of the uncanny home. Pins and needles pierce the curtain to mark the passing of time, referencing a cell-bound prisoner. Dust, memories and conversations are trapped within its sieve-like net. Experiences of claustrophobia, confinement and coercion are made manifest through the domestic veil of the net curtain.